Misconceptions of Organic Chemistry Concepts Held by Elementary Students after Slovak School Reform - Mĺkva, Monika; Held, Ľubomír (Scientia in educatione, 2020)
Many research reports have proved that pupils hold misconceptions in majority of chemistry fields and have also problems to understand many of chemical concepts. Misconceptions are strongly anchored in students’ cognitive structures, they are durable, resistant to change and not easy to be eradicated. Our contribution demonstrates students’ misconceptions in the field of organic chemistry. It presents qualitative research of students’ misconceptions and knowledge in the field of organic chemistry conducted at Slovak schools. It specifies many of students’ misconceptions and findings in this area of chemistry. It also puts forward several recommendations for elimination of students’ misconceptions in the field of science, for making the teaching-learning process more effective and closer to students, to increase their interest toward study of science and their intrinsic motivation.